Nolobranti tourism development in Wangkal village Gading district of Probolinggo regency become agroeduwisata - Haryadi, Nanang; Hari Purnomo; Wildan Muhlison; Titin Agustina (Talenta Publisher, 2022)
Wangkal Village is one of the villages in Gading District of Probolinggo Regency that has agricultural potential that supports tourism development. Agricultural potential includes abundant water conditions so that people prefer to grow rice every year and be used for freshwater fish cultivation. Another potential that now exists in Wangkal village is the Nolobranti River Tubing tour. This tour offers the concept of tubing down the river along the village of Wangkal. This tour in the dry season is less running because the water discharge is reduced. The Wangkal village government wants to develop agricultural potential and serve as a center for education for the community and tourists who are traveling in Nolobranti. The problem of nolobranti tourism development, among others, this tourist spot only provides river tubing packages. Therefore, it is necessary for the development of nolobranti tourism to become a place of education in the field of agriculture by developing freshwater fisheries combined with rice farming and becoming an educational center for organic agricultural startups. The hope is that this tourist area will not only become a tourist transit, but also a place of education as an agroeduwisata. Agroeduwisata area will be able to offer tour packages, among others: farming various types of vegetables, getting to know sewage treatment, getting to know fish and livestock cultivation, making biopesticides, biofertilizers, packages feeding freshwater fish, airy tours about organic agricultural systems or rice minas, business motivation and other trainings. The results of the service activities show that the community has been able to produce biological products such as making biopesticides, learning the cultivation of black flies to process waste and freshwater cultivation combined with aquponics and mina padi (rice-fish integrated farming system).